Ostracod-based paleoenvironment inferences for the Jordan River Dureijat archaeological site, Northern Israel. - Björgvin Valdimarsson 1994- (2017)
Jordan River Dureijat (JRD), an Epipaleolithic site on the Eastern bank of the Jordan River in Israel can potentially shed light on relatively unknown paleoenvironment characteristics of the area during the Late Glacial period and the early and late part of the Holocene. From twenty samples at the main sections of the archaeological site Jordan River Dureijat (JRD) ostracod valves and carapace were collected and subsequently counted and identified at the University of Iceland. The results from the study of JRD ostracod taxa and total valve concentrations indicated that the environment and water habitat around the JRD site was a lake-shore setting prone to lake level changes. The marginal lake setting consisted of freshwater in its strict sense inferred for most samples and possibly slightly brackish water inferred for the uppermost modern sample (no.20). Mainly ostracod valves representing freshwater dwellers were recorded at the JRD site. These inferences are based on the application of a transfer function to the fossil ostracod assemblages from the JRD site. This water habitat had probably not a dense aquatic vegetation cover due to the low abundance of Cypridopsis vidua shells. Seasonal fluctuations in the habitat are apparent by the presence of Heterocypris salina and Humphcypris subterranea but the lake was apparently not completely drying during the hotter seasons inferred from the presence of Darwinula stevensoni valves in every sample. There are also some changes of the lake shore throughout the study area with an environment more like the modern Sea of Galilee in the uppermost Holocene layer and with Ilyocypris salebrosa only present in samples 35-99, it shows that change occurred during Late Glacial-Early Holocene period. The finds of this thesis show the paleoenvironment changes during the last ~20.000 cal yr BP to ~11.500 cal yr BP and gives a unique opportunity to compare Late Glacial and Holocene conditions to the JRD modern day characteristics. Jordan River Durejiat(JRD) er Epipaleolithic ...